Remarks on Receiving the 2000 Special Merit Award - Rhys B. Jones, DDS, MS (Blackwell Synergy, 2001)
Alex, thank you very much for those kind remarks and this very special award. It is indeed a great honor to be recognized by your peers and professional organization, an organization whose work is so vital to the improvement of the nation’s health.